Social demography and eating patterns to the risk of stunting - Heni Puji Wahyuningsih; Yuni Kusmiyati (Jurnal Kesehatan Ibu dan Anak, 2020)
Stunting is a long-term manifestation of low-quality diet consumption factors, recurrent infectious diseases, and the environment. Stunting in infants needs special attention because it can hamper physical growth, mental development and health status in children. This study aims to determine the social demographic effects and feeding patterns on the risk of stunting. This research is a quantitative study with a retrospective cohort test design and using concetutive sampling. The total sample in this study were 177 case groups and 177 control groups. The instrument used in this study was a questionnaire that caused stunting. Analysis of the data used in processing the questionnaire is chi square analysis and logistic regression analysis with an accuracy rate of 95%. As for testing the influence of factors using path analysis. Based on the results of the path analysis test it is known that the pattern of feeding (b = 0.213; SE = 0.034; p <0.001), gender (b = 0.095; SE = 0.50; p <0.001), number of working family members (b = 0.103; SE: 0.046, p <0.005), number family members (b = 0.028; SE = 0.023; p <0.001) and mother's work (b = 0.018; SE = 0.029; p <0.000) have a direct effect on stunting risk. which means that every increase in one unit of working mothers will affect the reduction in stunting. Meanwhile, mother's education has an indirect effect on stunting, but mother's education has a direct effect on feeding patterns (0.041; SE = 0.067; p <0.001). This study shows that the variables of gender, number of families, work of mothers, number of working families, and quality of life of children have a direct and significant effect on stunting risk, while mother's education has an indirect influence over dietary factors.